2011
DOI: 10.1063/1.3642997
|View full text |Cite
|
Sign up to set email alerts
|

The significance of in situ conditions in the characterization of GaSb nanopatterned surfaces via ion beam sputtering

Abstract: A systematic study is conducted in order to elucidate the underlying mechanism(s) for nanopatterning with low-energy irradiation of GaSb (100) under normal incidence. Ion energies between 50 and 1000 eV of Arþ and ion fluences of up to 10 18 cm À2 were employed. Characterization of the shallow (e.g., 1 to 6 nm) amorphous phase region induced by irradiation and the subsurface crystalline phase region is accomplished with low-energy ion scattering spectroscopy and x-ray photoelectron spectroscopy, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…An important prediction from [243,244] is that composition segregation will lead the high-yield species to remain at the top of the structures produced, as has been reported for experiments on GaSb dot formation, in which ripple peaks are reported to be Sbrich [51]. This is a consequence of the fact that, due to the BH instability, ripple troughs are eroded more efficiently, and therefore they become depleted in that species that sputters faster.…”
Section: Two-field Composition Modelsmentioning
confidence: 82%
See 2 more Smart Citations
“…An important prediction from [243,244] is that composition segregation will lead the high-yield species to remain at the top of the structures produced, as has been reported for experiments on GaSb dot formation, in which ripple peaks are reported to be Sbrich [51]. This is a consequence of the fact that, due to the BH instability, ripple troughs are eroded more efficiently, and therefore they become depleted in that species that sputters faster.…”
Section: Two-field Composition Modelsmentioning
confidence: 82%
“…Hence, all the patterns described in this section will be rippled structures. There are, however, some especial cases in which ordered Si nanodots can be obtained for very low levels of impurities [51][52][53] or on clean targets [54]. These examples are interesting for device applications in which nanostructured impurity-free silicon surfaces are required.…”
Section: Low-energy ( < 10 Kev)mentioning
confidence: 99%
See 1 more Smart Citation
“…In their view, preferential sputtering of antimony leads to segregated regions of gallium at the surface of the solid; these in turn shield the underlying gallium antimonide from the incident ions, leading to the development of cones with gallium dots at their apices. It is unclear whether the surface really is enriched in gallium, however [1,27]. Moreover, the simulations of Le Roy and co-workers were confined to two dimensions [26], and so it is not currently known whether or not their model leads to orderly arrays of nanodots in three dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the fact that there was no direct experimental evidence of Sb being preferentially sputtered, SRIM 12 calculations based on a linear cascade and a binary collision approximation (BCA) have shown both Ga and Sb sputters at the same magnitude. 13 Le Roy et al 14,15 suggested another mechanism that is based on Ga surface segregation to the surface during the early stage growth stages of the structures. According to this study, Ga segregates to the surface and form Ga shields (islands) on the surface.…”
Section: Introductionmentioning
confidence: 99%